The playing field of the text in the artpractice of the “last avant-garde artist”, Sergei Maslov - G. G. Gizdatov (Шаги)
The article examines the forms and functions of the text in the artistic practice of S. N. Maslov (1952–2002), a representative of contemporary art in Kazakhstan. Based on the material of the artistic avant-garde in Kazakhstan, text-centricity and literature-centricity as universal properties of late Soviet and post-Soviet visual culture are analyzed for the first time. The texts created by the Kazakhstani author in various modifications of contemporary art were chronologically different: they appeared before, during and after the creation of the visual image. The features identified in the article include the creation by this post-avant-garde author not so much of a work-result, but more of a work-process, with the author’s obligatory manipulation of the text in space and time, when artistic practice turns into a multilayered game in front of the audience (readers). The article presents how Sergei Maslov managed to capture and convey through the text, woven by him into the plot of his artistic actions, the main issues in the specifics of post-Soviet existence and daily life, and then to transform them into the aesthetics of absurdity. One of these ways, as shown in the article, was the use of the aesthetics of mass media forms of the text: traditional writing, bureaucratic instructions and the horoscope, as well as the form of a multimedia novel. The art practice of S. N. Maslov reflected his characteristic literary centrism with the simultaneous access of this artist and performer to the features of the modern digital artistic environment.